PENGARUH PEMBELAJARAN BERDIFERENSIASI, BUDAYA ORGANISASI TERHADAP KETERAMPILAN MOTORIK SISWA INKLUSI DI SLB BC BUDI LESTARI TANGERANG SELATAN - Surasni; Luqman Rohmad Maghribi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the multidimensional learning barriers faced by inclusive students at SLB BC Budi Lestari, particularly regarding low motor skills which are often hindered by conventional pedagogical strategies and communication anxiety (glossophobia). The purpose of this study is to evaluate the influence of differentiated instruction and organizational culture on the motor skills of inclusive students. Using a quantitative associative approach, data were collected through motor performance tests and questionnaires from teachers and students. The results indicate a significant and positive influence, both simultaneously and partially, of differentiated instruction and organizational culture on students' motor skills. The integration of Artificial Intelligence (AI) features as a creativity stimulant and the use of local wisdom (Majalengka Wisdom) in differentiated learning were found to significantly reduce students' psychological barriers. Furthermore, a professional school ecosystem supported by transparent financial management (Balance Score-Card) and reflective academic supervision provides the necessary systemic foundation for optimizing student development. This study confirms that a synergy between adaptive pedagogy and a supportive organizational culture is essential for achieving student independence in the era of educational change.